Facilitating patients with disorders of consciousness to sit without trunk support: a qualitative study. Issue 17 (25th March 2015) - Miyata, Kumiko; Yoshimura, Sadako; Hayashi, Yuko
<x xml:space="preserve">Abstract</x> Aims and objectives This study aimed to clarify why and how clinical nurses facilitate sitting without trunk support among patients with disorders of consciousness. Background Recent attention has focused on encouraging patients with disorders of consciousness to sit without trunk support, but no reports describe this intervention among patients with poor awareness and physical disuse. Design Qualitative research design. Methods We enrolled five clinical nurses with interventional experience in rehabilitating patients with disorders of consciousness to sit without trunk support. Participant observation and semi‐structured interviews were used to collect data. The data were analysed by text‐mining method. Results Three reasons for nursing in the sitting position were identified: to raise the patient's body to assess the recovery of activities of daily living, to adjust their circadian rhythm and encourage the will to sit, and to make it easier to breathe. Five practices were identified: moving the patient to the prone position to sit in safety and comfort, developing postural stability by improving the flexibility of the lower limbs, improving the flexibility of the hip joints, developing trunk balance and encouraging hand use for stability, and ensuring safety by terminating the sitting practice when symptoms of respiratory failure, heart failure, or excessive tiredness developed. Conclusions The rationale for nursing patients with disorders of consciousness to sit without trunk support was to establish a foundation for independent living. This was achieved by preparing patient's disused body for activity by improving the flexibility of hip joint in the prone position. This represents a new intervention for patients with disorders of consciousness that could facilitate independent living. Relevance to clinical practice This study provides empirical and practical evidence from nurses who perform novel clinical interventions that specifically promote independent living. Further accumulation of quantitative clinical results and physiological verification are required.